Design and Tuning PID Fuzzy Controllers for Armature-controlled DC Motors - Natsheh, Essam (International Journal of Human and Technology Interaction (IJHaTI), 2018)
Design and tuning PID fuzzy controllers is an active research field looks for the optimal design for these controllers. In this paper, we propose a novel optimization design method that is using performance rule-based model with any design method of the PID fuzzy controllers to satisfy certain desired performance. Since constructing the membership functions is the most critical part of the fuzzy controller, a self-optimized membership functions algorithm is introduced. Armature-controlled DC motors, as an application representing second-order systems, was used to analyze the performance of the proposed design method and compare its performance with other various design methods. The accuracy analysis shows that the proposed design methods is 2 seconds faster in rise-time, 2 seconds faster in settling-time and, at the same time, it decreases the overshot 1.7% than the original design methods. Meanwhile, the robustness analysis shows that the proposed design methods is 2 seconds faster in rise-time, 2.6 seconds faster in settling-time and, at the same time, it decreases the overshot 3.4% than the original design methods.